2015
DOI: 10.2147/ndt.s79707
|View full text |Cite
|
Sign up to set email alerts
|

Do physical exercise and reading reduce the risk of Parkinson’s disease? a cross-sectional study on factors associated with Parkinson’s disease in elderly Chinese veterans

Abstract: BackgroundThe purpose of this study was to investigate risk factors for and factors protecting against Parkinson’s disease (PD) in elderly Chinese veterans.MethodsUsing a database containing detailed information on the health status of the nervous system in elderly Chinese veterans, univariate and multivariate analyses of factors that may be associated with PD were performed. Univariate analysis of qualitative data was done using the Pearson Chi-square and Fisher’s exact tests, and the Mann–Whitney U nonparame… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 52 publications
0
7
0
Order By: Relevance
“…The association of physical activity and risk of PD has been recently investigated in two Eastern case‐control studies from China. A reduced PD risk was observed in both the studies …”
Section: Analytical Epidemiologymentioning
confidence: 57%
See 1 more Smart Citation
“…The association of physical activity and risk of PD has been recently investigated in two Eastern case‐control studies from China. A reduced PD risk was observed in both the studies …”
Section: Analytical Epidemiologymentioning
confidence: 57%
“…78,108 Case-control studies 2 case-control studies performed in China; both studies showed showed a reduced risk for PD (OR 0.20-0.48). 49,82 1 case-control study performed in the USA showed that physical activity was associated with reduced risk for PD: OR 0.50 to 0.64 depending on the age in which the person engaged in physical activity. 109 1 case-control study study performed in the USA showed that certain occupations associated with high physical activity was associated with reduced risk for PD.…”
Section: Physical Activitymentioning
confidence: 99%
“…This is not surprising, however, since PA stimulates the synthesis of DA and trophic factors, which promote neuroplasticity and inhibit apoptosis and inflammation, thereby delaying the progression of PD symptoms (Monteiro-Junior et al, 2015). In addition, epidemiological studies report that leading an active lifestyle reduces the risk of developing PD by approximately two fold (Zou et al, 2015).…”
Section: Anti-inflammatory Effects Of Physical Activity and Exercise mentioning
confidence: 99%
“…Experimental and epidemiological studies have demonstrated that living a healthy and physically active lifestyle reduces the risk (Barnes and Yaffe, 2011;Scarmeas et al, 2009;Zou et al, 2015) and severity of neurological diseases (Archer and Kostrzewa, 2015;Canning et al, 2015;Erickson et al, 2012;Eyre and Baune, 2012;Frazzitta et al, 2015;Frazzitta et al, 2014;Liu et al, 2013;Radak et al, 2007;Radak et al, 2013;Suijo et al, 2013;Uc et al, 2014;Yu et al, 2014). However, the cellular and molecular mechanisms responsible for these beneficial effects of PA have not been established.…”
Section: Summary and Hypothesesmentioning
confidence: 99%
“…1 It is the second most common neurodegenerative disease in the elderly, with an estimated prevalence of 3.3% in Brazil. 2 There are 17.4 cases per 100,000 people per year, while among people aged between 50 and 59 there are 93.1 cases per 100,000 people per year.…”
Section: Introductionmentioning
confidence: 99%